Fantasy of meat consumption and buoyant meat market in Kohima, Nagaland - IMCHEN, IMLIMENLA; SAHARIA, K K; DUTTA, J B; SAIKIA, J K; BORA, L (The Indian Journal of Animal Sciences, 2015)
In view of the much acclaimed saying that Nagas are heavy meat eaters, a study was carried out in the capital city of Kohima, Nagaland State with twin objectives of categorizing the meat consumers in the area and to estimate the expenditures on meat. With a pre-tested, reliable and valid interview schedule, data were collected personally by tracking back the meat consumers from different meat markets in Kohima. As many as 100 meat customers and 30 sellers were interviewed to make the sample size 130. Meat consumers in Kohima, Nagaland consumed meat from both conventional and non-conventional origin much higher than the recommended level. It was around 27 kg/family/month in a family of about 4 to 5 members. Therefore, total meat consumption per month both conventional and non-conventional was a matter of considerable concern for the state’s exchequer. Further majority of the population fell under the medium to high meat consuming groups. There was also zone-wise mean difference among meat consumers while there was no significant mean difference between the meat customers and the sellers. A total expenditure of Rs 1,393,092.96/ day in the capital city was made on meat. Assuming local production at the rate of 25%, the deficit per day was Rs 1,044,819.72. This however, exposed two facts quite apparently that, one - people in Kohima, Nagaland had a necessity to re-learn about consumption of meat in and around recommended level and two - there is a huge scope for production of meat yielding livestock and poultry in and around Kohima, Nagaland.